Educação do campo: territórios, escolas do campo e formação dos professores em Teixeira de Freitas-BA - Cleper de Arruda Lima (2018)
This research has as objective generality searches and to analyze as the Education of the Field has happened in the territories of the town of Santo Antônio, Agricultural Community Rural Volta da Perna e Assentamento Bela Manhã in the city of Teixeira de Freitas-BA, also searching to analyze and to mapear the challenges presented for the professors who work in the situated schools in the three territories where the research if developed, it was possible to investigate as the professors and the teachers of each territory understand the schools of the field of the city where they work and to identify and to analyze which actions of formation you specify, are being developed for the net municipal theatre of education for its professors. In this inquiry the theoretical recital argued on aspects the formation of the Brazilian field, the concept of territory and its diversities, the description of the education of the field and the formation of its professors. In the development of the research we stand out that this inquiry was of qualitative matrix and as metodológicas tools for collection of data we work with sampling in three schools of city being one in each investigated territory and the citizens of the research had totalized six two of each school, that we apply, interview, structuralized questionnaires, also in the collection of data we had and analyzes documentary. With the collected data we construct three categories of you analyze being: the challenges of each territory; the school of the field of each territory; e the teaching formation. From these categories it was possible to identify that in the three categories analyzed the territory they present approaches and distanciamentos between itself thus the initial hypothesis of our inquiry did not confirm total, this because we believed that the citizens of the schools of each investigated territory would present a distinct understanding on the questions of each category